2018
DOI: 10.1029/2018pa003494
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Paleoecology on the TEX86 Sea Surface Temperature Proxy in the Pliocene‐Pleistocene Mediterranean Sea

Abstract: The TEX86 proxy, based on the distribution of isoprenoid glycerol dialkyl glycerol tetraethers (iGDGTs) from planktonic Thaumarchaeota, is widely used to reconstruct sea surface temperature (SST). Recent observations of species‐specific and regionally dependent TEX86‐SST relationships in cultures and the modern ocean raise the question of whether nonthermal factors may have impacted TEX86 paleorecords. Here we evaluate the effects of ecological changes on TEX86 using one Pliocene and two Pleistocene sapropels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 84 publications
(246 reference statements)
4
37
0
3
Order By: Relevance
“…Currently available  13 C GDGT data and resulting  Ar calculations are consistent with the range of values predicted by our strict autotrophy model (Eqs. 8,9), in both the reported means of GDGTs and biphytanes as well as the specific isotopic values reported in recent studies that give emphasis to crenarchaeol as a planktonic thaumarchaeal biomarker (Pearson et al, 2016;Polik et al, 2018;Hurley et al, 2019).…”
Section: Biosynthetic and Community Effectsmentioning
confidence: 52%
See 1 more Smart Citation
“…Currently available  13 C GDGT data and resulting  Ar calculations are consistent with the range of values predicted by our strict autotrophy model (Eqs. 8,9), in both the reported means of GDGTs and biphytanes as well as the specific isotopic values reported in recent studies that give emphasis to crenarchaeol as a planktonic thaumarchaeal biomarker (Pearson et al, 2016;Polik et al, 2018;Hurley et al, 2019).…”
Section: Biosynthetic and Community Effectsmentioning
confidence: 52%
“…As currently modeled, the carbon isotope variation over reasonable marine CO 2 concentrations (e.g., 10-50 M) is expected to be ≤ 5‰ (Figure 3). For applications using  13 C measurements of GDGT lipids, our recent work using spooling-wire micro-combustion IRMS (SWiM-IRMS; Sessions et al, 2005) has a demonstrated precision and accuracy of 0.2‰ (1) for crenarchaeol isolated from relatively small samples of sediments, i.e., quantities that can be obtained from ocean drilling program core repositories (Pearson et al, 2016;Elling et al, in revision;Polik et al, 2018). When translated to uncertainty in [CO 2(aq) ] reconstructions, this analytical limitation alone implies that the  Ar proxy is unlikely to be useful under conditions of atmospheric pCO 2 > 1500 ppm ( Figure 5), implying it will be best suited to reconstruct episodes of Earth history in which the atmospheric CO 2 content was < 4 times the preanthropogenic Holocene level.…”
Section: Sensitivity Of  Ar To Variations In Pcomentioning
confidence: 99%
“…This complication affects application of such index values to environments in which there may be multiple variables experiencing simultaneous shifts caused by different environmental drivers (e.g., ref. (27)).…”
Section: Discussionmentioning
confidence: 99%
“…More fundamentally, in natural systems, it is likely that aggregated GDGT abundance variations in response to growth temperatures result from changing compositions of archaeal populations as well as the physiological response of individual strains to growth temperature (Elling et al 2015). For instance, a multiproxy study of Mediterranean Pliocene-Pleistocene sapropels indicates that specific distributions of archaeal lipids might be reflective of temporal changes in thaumarchaeael communities rather than temperature alone (Polik et al, 2018). Indeed, the potential influence of community switching on GDGT composition can be seen in mesocosm studies, with different species preferentially thriving at different growth temperatures (e.g., Schouten et al, 2007).…”
Section: $%mentioning
confidence: 99%
“…Overall, the failure of the nearestneighbour predictor to provide accurate temperature estimates even when the normalised distance to the nearest point is small, Dx,y ≤ 0.5, casts doubt on the possibility of designing an accurate predictor for temperature based on GDGT observations. This is most likely due to additional environmental controls on GDGT abundance distributions in natural systems, in particular the water depth (Zhang and Liu, 2018), nutrient availability (Hurley et al, 2018;Polik et al, 2018;Park et al, 2018), seasonality, growth rate (Elling et al, 2014) and ecosystem composition (Polik et al, 2018), that obscure a predominant relationship to mean annual SSTs.…”
Section: Nearest Neighboursmentioning
confidence: 99%